DIGITAL TRANSFORMATION OF LABOUR RELATIONS – THE FUTURE CHALLENGE - Jovevski, Lazar (Iustinianus Primus Law Review - Law faculty Justinijanus Primus, 2021)
In this paper, the author analyses the current changes that are taking place in the field of labour relations and labour law. The paper covers the previous experiences of digital transformation of labour relations that occurred in the pre-Covid era, on the one hand, as well as the impact of the Sars KOV 19 pandemic on this process today. The author in the paper pays special attention to the parallel digitalization process of the economy expressed through the so-called „the fourth economic revolution" and its impact on the transformation of labour relations in the region and Europe. The paper analyses the aspects of responsiveness of legal systems in Europe and the region of Southeast Europe in terms of acceptance or resistance to the digitalization of the economy and labour. The paper lists the positive aspects of the current and future digital transformation of labour relations, which means for workers, employers, as well as future government labour policies. The negative aspects are also analysed, as possible future challenges that will inevitably bring the digitalization of labour relations, among which the author emphasizes the growth of unemployment, weakening trade union influence, resistance from employees and the aspect of safety and health at work.
Keywords: digital transformation, employment, digits, economy